Contrastive Analysis of Noun Clauses in Arabic and Swahili Languages - Faisal Masoud Muhindo; Erfan Gazali (Indonesian Journal of Arabic Studies, 2022)
The focus of this study is to compare the structure of noun clauses in Arabic and Swahili based on its pattern and constituent elements. This study is a qualitative study using a contrastive descriptive analysis method. The analysis used is content analysis with the aim of describing the structure of noun clauses in Arabic and Swahili separately which is then compared to find out the similarities and differences in the noun clauses of the two languages. Based on the results of the comparison, it can be seen that the noun clauses of the two languages have the same structure, namely consisting of a subject and a predicative. The difference between these two noun clauses is that in Arabic (1) predicates can be nouns, adjectives, prepositional phrases, or adverbs and this is not found in Swahili; (2) subject and predicate in Arabic can be either masculine or feminine; (3) Subjects in Arabic sometimes take the form of definite and infinite (4) Nominal sentences in Swahili have 4 four kinds, namely sentensi sahili, sentensi ambato, sentensi changamano and sentensi shurtia while Arabic has two types of noun clauses namely mansukha and gairu mansukha. By knowing the similarities and differences of noun clauses based on patterns and forming structures, students can get a better description of how to use Arabic clauses correctly. For teachers of Arabic, this study can be input for teaching clauses and preparing better learning materials.